Fluorescence and electron transfer of Limnospira indica functionalized biophotoelectrodes - Ryzhkov, Nikolay; Colson, Nora; Ahmed, Essraa; Pobedinskas, Paulius; Haenen, Ken; Janssen, Paul J.; Braun, Artur (Photosynthesis research, 2024)
Cyanobacteria play a crucial role in global carbon and nitrogen cycles through photosynthesis, making them valuable subjects for understanding the factors influencing their light utilization efficiency. Photosynthetic microorganisms offer a promising avenue for sustainable energy conversion in the field of photovoltaics. It was demonstrated before that application of an external electric field to the microbial biofilm or cell improves electron transfer kinetics and, consequently, efficiency of power generation. We have integrated live cyanobacterial cultures into photovoltaic devices by embedding Limnospira indica PCC 8005 cyanobacteria in agar and PEDOT:PSS matrices on the surface of boron-doped diamond electrodes. We have subjected them to varying external polarizations while simultaneously measuring current response and photosynthetic performance. For the latter, we employed Pulse-Amplitude-Modulation (PAM) fluorometry as a non-invasive and real-time monitoring tool. Our study demonstrates an improved light utilization efficiency for L. indica PCC 8005 when immobilized in a conductive matrix, particularly so for low-intensity light. Simultaneously, the impact of electrical polarization as an environmental factor influencing the photosynthetic apparatus diminishes as matrix conductivity increases. This results in only a slight decrease in light utilization efficiency for the illuminated sample compared to the dark-adapted state.